1977
DOI: 10.1677/joe.0.0750145
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of Androgens in Vitro by the Submaxillary Salivary Gland of the Mature Domestic Boar

Abstract: Homogenates of the submaxillary glands of mature domestic boars were incubated with radioactively labelled C19 steroids. The metabolism of [7\g=a\-3H]dehydroepiandrosterone and [7\g=a\-3H]androstenedione was primarily to the end products 5\g=a\-androstane-3,17-dione and androsterone, but some testosterone, 5\g=a\-dihydrotestosterone and 5\g=a\-androstane-3\g=a\,17\g=b\-diol were also formed. When [7\g=a\-3H]5-androstene-3\g=b\,17\g=b\-diol was used as a substrate, the major metabolite was testosterone. Both [7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

1978
1978
1986
1986

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 26 publications
2
19
0
Order By: Relevance
“…There is evidence indicating that DHA and 5-androstenediol may be important precursors of testosterone in the pig testis (Ruokonen, 1978) as has been suggested for the testes of dogs (Yamaji, Motohashi, Tanioka & Ibayashi, 1968;Oh & Tamaoki, 1973) and men (Vihko & Ruokonen, 1975). However, there is also evidence indicating that, in the boar, 5-ene unsaturated C19 steroids may be important prohormones for testosterone in extragonadal tissues such as the submaxillary gland (Booth, 1977) and the accessory sex organs (Booth, 1980). Administration of 5-androstenediol to prepubertally castrated boars (2 mg/5 kg) maintained the accessory organs in a manner comparable to that produced by the same amount of testosterone (Booth, 1980).…”
Section: Introductionmentioning
confidence: 91%
“…There is evidence indicating that DHA and 5-androstenediol may be important precursors of testosterone in the pig testis (Ruokonen, 1978) as has been suggested for the testes of dogs (Yamaji, Motohashi, Tanioka & Ibayashi, 1968;Oh & Tamaoki, 1973) and men (Vihko & Ruokonen, 1975). However, there is also evidence indicating that, in the boar, 5-ene unsaturated C19 steroids may be important prohormones for testosterone in extragonadal tissues such as the submaxillary gland (Booth, 1977) and the accessory sex organs (Booth, 1980). Administration of 5-androstenediol to prepubertally castrated boars (2 mg/5 kg) maintained the accessory organs in a manner comparable to that produced by the same amount of testosterone (Booth, 1980).…”
Section: Introductionmentioning
confidence: 91%
“…The methanolic extract was subsequently subjected to the Brown's partition (Brown, 1955) to provide separate neutral and phenolic fractions. Androgens were isolated by a combination of thin-layer and paper chromatography (Booth, 1977) and the steroids were quantified by gas-liquid chromatography Booth (1975). Oestrone and oestradiol-17ß were separated from each other by thin-layer chromatography and quantified either by radioimmunoassay (Singh & Booth, 1978), for unconjugated oestrogens, or by gas-liquid chromatography (conjugated oestrogens) as described above.…”
Section: Steroid Determinationsmentioning
confidence: 99%
“…Some of these C19 steroids, notably dehydroepiandrosterone (DHA) and 5-androstenediol may be important precursors of testosterone in the pig testis, as they are in the testis of dogs (Yamaji, Motohashi, Tanioka & Ibayashi, 1968;Oh & Tamaoki, 1973) and man (Vihko & Ruokonen, 1975). These 5-unsaturated C19 steroids may also be prohormones for testosterone in androgen end-target organs, and Booth (1977) has shown that DHA and especially 5-androstenediol are readily converted to testosterone and 5a-reduced metabolites in the submaxillary salivary gland of the boar. This finding and other evidence (Booth, 1972(Booth, , 1975Booth, Hay & Dott, 1973) indicates that the submaxillary gland is an important androgen end-target organ in the male pig, modified to accumulate and release the pheromonal 16-unsaturated C19 steroids (16-androstenes).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent isolation and identification of radiometabolites were carried out, as described by Booth (1977), with the Bush A paper chromatography system to separate mono-and di-hydroxy metabolites of progesterone, and thin-layer chromatography (two runs with toluene:ethyl acetate (9:1 v/v), one run with benzene:ether (9:1 v/v) (Gower, 1964)) for non-polar steroids to separate 5a-from 5ß-pregnanedione.…”
Section: Steroid Metabolism In Blastocystsmentioning
confidence: 99%
“…Unlabelled oestradiol and oestrone (20 µg each) were added to each of the diethyl ether extracts, and the 83 % aqueous methanol extract (the petroleum ether phase was discarded), before evaporation to dryness by rotary vacuum evapora¬ tion. The residues corresponding to the blastocysts, uterine flushings and total uterine tissue were subjected to thin-layer chromatography with benzene:acetone (4:1 v/v), and the distribution of radioactivity on the chromatograms was located with a scanner as previously described (Booth, 1977); areas corresponding to oestradiol and oestrone were eluted for liquid scintillation counting.…”
Section: Transfer Of 3h-labelled Oestradiol To Blastocystsmentioning
confidence: 99%